Identification and functional analysis of a circular rna circznf800 involved in regulating colorectal cancer stemness properties - Vimalan, Rengganaten (2023)
Colorectal cancer (CRC) is one of the most diagnosed cancers. Effective therapeutic interventions remain challenging due to the existence of a rare population of chemoresistant CRC cancer stem cells (CrCSC). In a spheroidal culture model, the CrCSC population is enriched with enhanced CSC-like properties. However, the molecular events governing CSC properties in the CrCSC population remains poorly understood. Circular RNAs (circRNAs) are long non-coding regulatory RNAs associated with various biological functions. The present study aimed to elucidate the biological role of circRNAs in maintaining CSC properties in CRC cells. CircRNA sequencing was performed using Illumina technology. qRT-PCR and RNA FISH were used to evaluate the expression levels of circRNA. In vitro transcription and CRISPR Cas13d RNA editing system were used to modulate the expression levels of the circRNA. Whole-transcriptome sequencing of RNA of CRC spheroidal cells revealed over 8,000 differentially expressed circRNAs. The top 8 differentially expressed circRNAs were identified and the interacting miRNAs and mRNA transcripts were predicted. KEGG analysis revealed the enrichment of various CSC-associated signalling pathways; the pluripotency regulating pathways were most significantly up-regulated. Two circRNAs, hsa_circ_0066631 (circDCBLD2) and hsa_circ_0082096 (circZNF800), were predicted and experimentally validated to sponge five miRNAs, releasing posttranscriptional inhibition of six mRNA transcripts involved in the regulation of stemness. Literature analysis showed that the predicted miRNAs acted as tumour suppressors and the targeted transcripts regulated various CSC signalling pathways. As a candidate circRNA for further in-depth analysis, circZNF800 was shown to be significantly up-regulated in CRC tumour tissues. CircZNF800 overexpression promoted CSC phenotypes, including proliferation, expression of CSC and intestinal stem cell markers, and tumorigenicity, all of which were reversed by CRISPR Cas13d-mediated circZNF800 knockdown. CircZNF800 was shown to sponge miR-140-3p, miR-382 and miR-579 which, in turn, increased the levels of ALK7, FZD3 and WNT5A, which are involved in the regulation of CSC properties. In conclusion, circZNF800, identified in CrCSC circRNA profiling, was shown to participate in regulating CSC properties in CRC.